Full axillary lymph node dissection and increased breast epidermal thickness 1 year after radiation therapy for breast cancer. Issue 8 (8th November 2019) - Lin, Jolinta Y.; Yang, Xiaofeng; Serra, Monica; Miller, Andrew H.; Godette, Karen D.; Kahn, Shannon T.; Henry, Simone; Brown, Gabrielle; Liu, Tian; Torres, Mylin A.
Abstract: Background: We previously reported a prospective study showing axillary lymph node dissection (ALND) is associated with increased breast skin thickening during and 6 weeks post‐radiation therapy (RT), and now report ALND's long‐term impact at 1 year. Methods: Among 66 women who received whole breast RT after lumpectomy, objective ultrasound measurements of epidermal thickness over four quadrants of the treated breast were measured at five time points: before RT, week 6 of RT, and 6 weeks, 6 months, and 1 year post‐RT. Skin thickness ratio (STRA) was generated by normalizing for corresponding measurements of the contralateral breast. Results: A total of 2, 436 ultrasound images were obtained. Among 63 women with evaluable data at 1 year, mean STRA significantly increased at 6 months (absolute mean increase of 65%, SD 0.054), and remained elevated at 1 year post‐RT (absolute mean increase of 44%, SD 0.048). In multivariable analysis, ALND compared to sentinel lymph node biopsy, longer interval between surgery and RT, increased baseline STRA, and Caucasian race predicted for more severe changes in STRA at 1 year compared to baseline (all P  < .05). Conclusions: In the setting of whole breast RT, our findings suggest that ALND has long‐term repercussions on breast skin thickening.